Evaluating Vocational English Education in Rural Indonesia: A CIPP-Based Analysis of Curriculum Alignment, Communicative Competence, and Workplace Readiness - Muhammad Shiddiq; Murni Mahmud; Amra Ariyani (STIT Buntet Pesantren Cirebon, 2026)
This study examined the execution of vocational English instruction in a rural Indonesian vocational high school utilizing the Context, Input, Process, and Product (CIPP) evaluation framework, emphasizing curricular alignment, communicative competence, and job preparedness. The study examined the implementation of vocational English learning concerning contextual support, instructional inputs, classroom procedures, and learning outcomes within the framework of the Merdeka Curriculum and vocational education. The study utilized a qualitative descriptive-evaluative methodology and was conducted at SMKN 1 Tapalang in West Sulawesi, comprising 28 participants, including school officials, English teachers, students, and parents. Data were gathered by classroom observations, semi-structured interviews, and document analysis, and analyzed utilizing the interactive model of data condensation, display, and conclusion drawing based on CIPP dimensions. The results indicated that English acquisition was predominantly matched with vocational and workplace-oriented goals via ESP-based instruction and communicative learning methodologies. Competent educators, curriculum execution, and fundamental instructional resources facilitated the learning process; yet, deficiencies in infrastructure, digital integration, and genuine communicative assessment were still apparent. Students exhibited moderate enhancement in reading, writing, vocabulary acquisition, and functional communication abilities, although speaking and listening skills necessitated further reinforcement. This study enhances vocational English education research by emphasizing the significance of communicative assessment, workplace-oriented training, and the implementation of contextualized curricula in rural vocational schools.